GAMBARAN KECEMASAN IBU HAMIL TRIMESTER III DALAM MENGHADAPI PERSALINAN DI MASA PANDEMI COVID-19 - Zakiyah, Humairatun; Wahyuni, Sri; Lestari, Widia (Coping: Community of Publishing in Nursing; Vol 10 No 5 (2022): Oktober 2022, 2022)
Anxiety of pregnant women who will give birth during the Covid-19 pandemic can be in the form of fear of being infected with Covid-19, lack of friends or family visiting, worrying about being isolated if confirmed positive for Covid-19, and also worrying about whether the baby will be infected with the virus because of the risk of contracting Covid-19 very high at birth. The effects of anxiety on a pregnant woman and her fetus can be serious, leading to increased labor pains, prolonged labor, and tension during labour. Various types of complications can also occur during pregnancy, such as premature birth, low birth weight, stunted fetal growth, and postnatal complications are also possible. There are several things that can cause anxiety during pregnancy for example, being too anxious can also cause hypertension during pregnancy, preeclampsia, and gestational diabetes. This study aims to explore the anxiety of third trimester pregnant women in dealing with childbirth during the Covid-19 pandemic, especially in the work area of ??the Payung Sekaki Health Center Pekanbaru City. This study uses a qualitative research method with a phenomenological approach to study the experiences of pregnant women. Based on the criteria in accordance with the research objectives and based on data saturation, five participants were obtained using purposive sampling. Data collection used semi-structured interviews and data analysis to collect data. The study found that pregnant women had anxiety related to the hospital situation, anxiety due to confirmation of Covid-19, anxiety related to the condition of the baby after birth, and anxiety related to the mother's condition.